"Getting involved": A thematic analysis of caregivers' perspectives in Chilean residential children's homes. (May 2017) - Garcia Quiroga, Manuela; Hamilton-Giachritsis, Catherine
A large number of children around the world are currently living in residential children's homes and a central figure in those settings is the caregiver. The relationship children establish with their temporary caregivers can be a crucial factor in their lives. However, little research has been conducted with caregivers working in institutional settings regarding their experience and the relationship they establish with the children they care for. This article presents the results of a qualitative study conducted with 43 caregivers working in eight different residential children's homes in Chile. The information was gathered through focus groups, and thematic analysis was conducted. The results show that caregivers report their experience of work and their relationship with children very positively and that this is characterized by their emotional involvement with children. This perspective appears to differ from that observed in large institutions in Europe, where there is some evidence that a more impersonal approach is predominant. However, it is acknowledged that this is based on caregiver perceptions which may or may not reflect cultural variations. The conclusion highlights the potential positive impact that caregivers can have on children's lives, alongside some factors that negatively affect caregivers' work, which could inform policy and procedures in order to provide better care for these children who (for various reasons) remain in residential care rather than family-based care.